Fetal Heterotaxy with Tricuspid Atresia, Pulmonary Atresia, and Isomerism of the Right Atrial Appendages at 22 Weeks - Julia E. Solomon; John H. Stock; Randy R. Richardson; Norman H. Silverman (American Journal of Perinatology Reports, 2013)
Abstract We report the accurate prenatal diagnosis at 22 weeks gestation of right atrial isomerism in association with tricuspid atresia. Several distinctive sonographic features of isomerism of the right atrial appendages were present in this fetus: complex cardiac abnormality, ventriculoarterial discordance, juxtaposition of the aorta and the inferior vena cava to the right side, pulmonary atresia, and anomalous pulmonary venous return to the morphological right atrium. Tricuspid atresia, which is an extremely rare lesion within heterotaxy spectrum disorders, was present. Postnatal investigations confirmed all prenatally diagnosed abnormalities, with additional findings of pulmonary atresia with discontinuous pulmonary arteries and bilateral arterial ducts, asplenia, and bilateral eparterial bronchi. To our knowledge, tricuspid atresia in the setting of isomerism of the right atrial appendages has not previously been diagnosed or reported prenatally. Because of the complexity of cardiac lesions that may be present in cases of atrial isomerism, these disorders should be considered even if sonographic findings are uncommon or atypical.